Enhancing the Role and Effectiveness of Corporate Social Responsibility (CSR) Reports: The Missing Element of Content Verification and Integrity Assurance - Sethi, S. Prakash 1934-; Martell, Terrence F.; Demir, Mert (2017)
Corporate Social Responsibility (CSR) reporting by large corporations has witnessed phenomenal growth over the last two decades. The voluntary nature of these disclosures, however, has led to inconsistencies in reporting formats, treatment, and inclusion of various contextual elements, and a lack of robust measures pertaining to the quality and accuracy of the reports’ content. Efforts to address these drawbacks such as Global Reporting Initiative and ISO 26000 have proven unsatisfactory due to their primary emphasis on process for creating CSR reports without similar attention on measurement criteria to ensure robust implementation, or verify accuracy of information. This paper attempts to fill this gap in the literature. It uses a new framework—called the CSR-Sustainability Monitor®—of analyzing and evaluating the contents of CSR reports in a manner that allows for a single report to be compared with any other single group, and groups of reports based on industry, country-of-origin, and similar other groupings. Using data from the CSR reports of 614 large corporations worldwide, this study analyzes the character and scope of integrity assurance contained in these CSR reports. The analysis is further extended to explore some external factors that would explain variations in the assurance decision and the quality of integrity assurance in these reports.
Keywords: Credibility; Public Trust; Transparency; Corporate Reputation; Corporate Social Responsibility; Analytical and scoring frameworks; Integrity assurance; Sustainability reporting; CSR-S Monitor; CSR reports